2022
DOI: 10.1186/s13244-022-01191-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography in the assessment of post-stroke muscle stiffness: a systematic review

Abstract: Background Post-stroke muscle stiffness is a major challenge in the rehabilitation of stroke survivors, with no gold standard in clinical assessment. Muscle stiffness is typically evaluated by the Modified Ashworth Scale or the Tardieu Scale; however, these can have low reliability and sensitivity. Ultrasound elastography is an advanced imaging technology that can quantitatively measure the stiffness of a tissue and has been shown to have good construct validity when compared to clinically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…This study population had high baseline fatigue levels, which improved post-treatment but remained in the severe category [104]. The change was twice the MCID [90,105] and consistent with meta-analysis data regarding localised PBMT [71].…”
Section: Discussionsupporting
confidence: 83%
“…This study population had high baseline fatigue levels, which improved post-treatment but remained in the severe category [104]. The change was twice the MCID [90,105] and consistent with meta-analysis data regarding localised PBMT [71].…”
Section: Discussionsupporting
confidence: 83%
“…This study population had high baseline fatigue levels, which improved post-treatment but remained in the severe category [77]. The change was twice the MCID [97,106] and consistent with meta-analysis data regarding localised PBMT [134]. Fatigue is multidimensional and its aetiological mechanism is not fully understood [13].…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, studies did not reliably show that quantitative stiffness correlates to symptom burden in the FM population [ 132 , 133 ]. Recent studies have shown promise in this technique in assessing post-stroke stiffness [ 134 ], but further research to validate this technique in the FM population is warranted.…”
Section: Discussionmentioning
confidence: 99%